2021
DOI: 10.22430/21457778.1826
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of a Scale to Measure the Job Satisfaction of Professors at Public Universities in Central Mexico during COVID-19

Abstract: Until May 2021, six and a half million deaths had been directly and indirectly associated with COVID-19. This pandemic has impacted the traditional classroom by transferring it to online environments. The objective of this study was to establish the construct validity of an instrument that measures professors’ job satisfaction. A cross-sectional psychometric study was carried out with a selection of 100 professors from public universities in central Mexico. Three main factors were found to explain 56% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As previous studies have pointed out [47], the COVID-19 pandemic forced the different educational institutions to transfer their classes to the virtual system, which also brought changes in interactions and students' perceptions of the instructional processes [47,69], and, in turn, could have had an impact on the construct validity of the instrument; however, the structure of the Spanish language version of the Life Skills Ability Scale, grouped into eight factors and a second order factor, corresponds to the original theoretical conception of the scale [2], which provides evidence of nomological validity. In this sense, studies that have tested construct validity in other instruments in the context of pandemics [70][71][72] have used confirmatory factor analyses, the same analyses performed in the present study. With respect to convergent validity, although, in this study, the scale presented was not associated with other instruments, it is possible to demonstrate that the relationships between the factors are positive and significant both in study 1 and 2, and between gender, while, with respect to discriminant validity, and although there was no other contrast instrument, it is possible to point out that, since there are significant differences between gender, the instrument presented is stable in the factors despite the differences between means, so it is capable of discriminating between gender.…”
Section: Overall Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies have pointed out [47], the COVID-19 pandemic forced the different educational institutions to transfer their classes to the virtual system, which also brought changes in interactions and students' perceptions of the instructional processes [47,69], and, in turn, could have had an impact on the construct validity of the instrument; however, the structure of the Spanish language version of the Life Skills Ability Scale, grouped into eight factors and a second order factor, corresponds to the original theoretical conception of the scale [2], which provides evidence of nomological validity. In this sense, studies that have tested construct validity in other instruments in the context of pandemics [70][71][72] have used confirmatory factor analyses, the same analyses performed in the present study. With respect to convergent validity, although, in this study, the scale presented was not associated with other instruments, it is possible to demonstrate that the relationships between the factors are positive and significant both in study 1 and 2, and between gender, while, with respect to discriminant validity, and although there was no other contrast instrument, it is possible to point out that, since there are significant differences between gender, the instrument presented is stable in the factors despite the differences between means, so it is capable of discriminating between gender.…”
Section: Overall Discussion and Conclusionmentioning
confidence: 99%
“…With respect to convergent validity, although, in this study, the scale presented was not associated with other instruments, it is possible to demonstrate that the relationships between the factors are positive and significant both in study 1 and 2, and between gender, while, with respect to discriminant validity, and although there was no other contrast instrument, it is possible to point out that, since there are significant differences between gender, the instrument presented is stable in the factors despite the differences between means, so it is capable of discriminating between gender. Nevertheless, as related research has suggested [70][71][72], it is necessary to continue testing the instrument to corroborate its construct validity at postpandemic times.…”
Section: Overall Discussion and Conclusionmentioning
confidence: 99%
“…Such findings assume a continuity between primary and secondary socialization, whether in a collectivist or individualistic sense, favorable or unfavorable , the principles that guide the individual in a family group would be the same ones that guide them in a labor or productive group [28]. In light of these results, work commitment would be the last link, at least in the workplace, in a chain of perceptions, beliefs, attitudes, decisions and actions directed from the primary group in which the individual learned the basic symbols and , in whose development, he never had the opportunity to question those principles that now seem to guide his commitment, productivity and job satisfaction [29]. In summary, the state of the art seems to show solid evidence regarding the complementarity between primary socialization and secondary socialization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to clarify the dimensions of organizational commitment from the complexity that the practice of Social Work implies [30]. This study seeks to establish the dimensions of work commitment considering levels of institutional complexity that framed the nonconformity with indicators of a commitment derived from primary socialization.…”
Section: Introductionmentioning
confidence: 99%
“…electronic networks such as Facebook, Youtube, Twitter and WhatsApp [9]. In this sense, the diversification of factors that make up the adhesion process implies the convergence of the media spheres with the personal, family, work and institutional spheres [10]. In this way, the adherence structure will include dimensions related to each area, as well as the allusion to their hybrid combinations such as vaccines, their percentage of effectiveness and the attribution to the government that people associate with the quality of immunization.…”
Section: Introductionmentioning
confidence: 99%